2017
DOI: 10.1039/c7ra10127a
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted one-pot synthesis in water of carbonylpyrazolo[3,4-b]pyridine derivatives catalyzed by InCl3 and sonochemical assisted condensation with aldehydes to obtain new chalcone derivatives containing the pyrazolopyridinic moiety

Abstract: Pyrazolo[3,4-b]pyridines derivatives have been synthesized via one-pot condensation of 3-methyl-1-phenyl-1H-pyrazolo-5-amine (1), paraformaldehyde (2) and β-diketones (3) under microwave irradiation in aqueous media catalyzed by InCl3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
(45 reference statements)
0
22
0
1
Order By: Relevance
“…In 2017, Gutiérrez group employed indium trichloride in water under microwave irradiation [39] for the construction of Pyrazolo[3,4‐b]pyridine derivatives 15 a – i via one‐pot three components tandem reaction of 3‐methyl‐1‐phenyl‐1H‐pyrazolo‐5‐amine 12 , formaldehyde 13 and β‐diketones 14 (Scheme 4).…”
Section: Multicomponent C−c and C−n Bond Forming Reactionsmentioning
confidence: 99%
“…In 2017, Gutiérrez group employed indium trichloride in water under microwave irradiation [39] for the construction of Pyrazolo[3,4‐b]pyridine derivatives 15 a – i via one‐pot three components tandem reaction of 3‐methyl‐1‐phenyl‐1H‐pyrazolo‐5‐amine 12 , formaldehyde 13 and β‐diketones 14 (Scheme 4).…”
Section: Multicomponent C−c and C−n Bond Forming Reactionsmentioning
confidence: 99%
“…Compounds 102 were also prepared by the reaction of the same reactants in the presence of diammonium hydrogen phosphate as a catalyst under conventional heating condition in good yields 85% to 95% (Scheme 55). [135] [137] reported the synthesis of pyrazolo [3,4-b] quinolin-5(6H)-one 107 by the reaction of formaldehyde with 3-methyl-1-phenyl-1H-pyrazolo-5-amine 106 and cyclohexane-1,3-diones 72 and 72a under microwave irradiation in aqueous media catalyzed by InCl 3 (Scheme 57).…”
Section: Pyrano[43-b]pyransmentioning
confidence: 99%
“…Molbank 2019, 2019, x 2 of 6 substituted pyrazole, formaldehyde, and β-diketone under 300 W microwave irradiation [18]. However, the use of a microwave reactor in one-pot synthesis of pyrazoline from substituted benzaldehyde, acetophenone, and phenylhydrazine has not been reported previously.…”
Section: Synthesis Of Compoundmentioning
confidence: 99%
“…Other researchers have also reported one-pot synthesis of pyrazolines from various starting materials and methods such as from 3-butynol and substituted phenylhydrazine under reflux condition [12], from substituted acetophenone, benzaldehyde, and phenylhydrazine under reflux condition [13,14] and through the formal [4 + 1] annulation reaction of 3-bromooxindoles and in situ-derived 1,2-diaza-1,3-dienes by stirring at room temperature [15]. In addition, it has also been reported that the one-pot synthesis of pyrazolines can be performed by reacting pyridine based chalcone and hydrazine hydrate under 300 W microwave irradiation [16]; by reacting substituted chalcone, hydrazine hydrate, and acetic anhydride under 550 W microwave irradiation [17]; and by reacting substituted pyrazole, formaldehyde, and β-diketone under 300 W microwave irradiation [18]. However, the use of a sealed-vessel reactor in one-pot synthesis of pyrazoline from substituted benzaldehyde, acetophenone, and phenylhydrazine has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%